2018
DOI: 10.1177/1049732318814542
|View full text |Cite
|
Sign up to set email alerts
|

Looking Through Dementia: What Do Commercial Stock Images Tell Us About Aging and Cognitive Decline?

Abstract: Commercial stock images are existing, artificially-constructed visuals used by businesses and media outlets to articulate certain values, assumptions and beliefs. Despite their pervasiveness and accessibility, little is known about the ways in which stock images communicate meanings relating to health and illness. This study examines a broad range of common stock images which depict dementia and aging, revealing the tendency for older people with dementia to be represented in objectifying and de-humanising ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 73 publications
2
27
0
1
Order By: Relevance
“…The responsibility for cognitive health and the blame for cognitive decline in old age might be shifted onto those who do not follow health and prevention recommendations and thus fail or refuse to live their lives in a healthy, active, and socially acceptable manner (Forlini & Hall, 2017). In interaction with degrading and objectifying images of dementia (Harvey & Brookes, 2019;Low & Purwaningrum, 2020), the strong emphasis on individual responsibility might support "victim-blaming of those living with dementia and result in increased stigmatization" (Lawless et al, 2018(Lawless et al, , p. 1548; see also Harris et al, 2016;Mohr et al, 2021;Peel, 2014). The responsibilization of cognitive aging could hence contribute to new forms of ageisms which replace the earlier general angst of aging with a specific fear of frailty, inability, and loss of cognitive abilities (Holstein & Minkler, 2003), and reinforce a devaluation of those who, due to physical and cognitive decline, can no longer comply with the ideal of self-reliant, successful aging.…”
Section: Stigmatizationmentioning
confidence: 99%
“…The responsibility for cognitive health and the blame for cognitive decline in old age might be shifted onto those who do not follow health and prevention recommendations and thus fail or refuse to live their lives in a healthy, active, and socially acceptable manner (Forlini & Hall, 2017). In interaction with degrading and objectifying images of dementia (Harvey & Brookes, 2019;Low & Purwaningrum, 2020), the strong emphasis on individual responsibility might support "victim-blaming of those living with dementia and result in increased stigmatization" (Lawless et al, 2018(Lawless et al, , p. 1548; see also Harris et al, 2016;Mohr et al, 2021;Peel, 2014). The responsibilization of cognitive aging could hence contribute to new forms of ageisms which replace the earlier general angst of aging with a specific fear of frailty, inability, and loss of cognitive abilities (Holstein & Minkler, 2003), and reinforce a devaluation of those who, due to physical and cognitive decline, can no longer comply with the ideal of self-reliant, successful aging.…”
Section: Stigmatizationmentioning
confidence: 99%
“…Another topic for future research pertains to the similarities and differences between newspapers' coverage of obesity and COVID-19 with respect to their political leanings, which I have not had space to analyse systematically in this article. Finally, images can function as powerful connotators of ideologies relating to health and illness (Harvey & Brookes, 2019). The corpus approach I took in this study did not facilitate the analysis of the images featured in the articles in my data.…”
Section: Discussionmentioning
confidence: 99%
“…the mental concept it represents) enables uncovering the meaning the sign represents (Saussure 2011). For example, social semiotic studies focused on dementia media discourses have examined stock images (Harvey and Brookes 2018), films (Zeilig 2014;Medina 2014), magazine and newspaper articles (Peel 2013;Kessler and Schwender 2012;Clarke 2006). Studies reported how the media mainly represent sick older women with dementia who need their dutiful female carer (Clarke 2006;Harvey and Brookes 2018).…”
Section: Semioticsmentioning
confidence: 99%
“…Media critics have suggested that people living with dementia are often portrayed using negative and sometimes positive stereotypes ( Van Gorp and Vercruysse 2012). Table 1 captures the negative representations of cultural themes that frame "demented" sufferers who look withdrawn, are losing their identity and humanity, invaded by the disease, a terrible destiny that awaits or call for constant care and burdens the family (Braun and Clarke 2006; Van Gorp and Vercruysse 2012;Harvey and Brookes 2018). Currently, it is unknown how and if people living with dementia are represented using technology, however older adults are often represented as not understanding technology (Joyce et al 2015).…”
Section: Semioticsmentioning
confidence: 99%